New Perspectives on Titanium Dioxide and Zinc Oxide as Inorganic UV Filters: Advances, Safety, Challenges, and Environmental Considerations - Stephany Mayumi Araki; André Rolim Baby (Cosmetics)
Exposure to ultraviolet (UV) radiation is a primary risk factor for various skin disorders, including erythema, sunburn, and skin cancer. Sunscreens containing UV filters, categorized as organic or inorganic, are widely utilized to mitigate these effects. Among inorganic UV filters, titanium dioxide (TiO2) and zinc oxide (ZnO) are prominently used due to their favorable safety and achievable broad-spectrum protection profiles. This review focuses on the properties, safety, and efficacy of TiO2 and ZnO in sunscreens, emphasizing their mechanisms of action, photostability, and impacts on human health and the environment. Key factors influencing their performance include particle size, surface coatings, and formulation pH. Despite recognized advantages, concerns about toxicity—particularly related to nanoparticle penetration and reactive oxygen species generation—highlight the need for robust safety assessments. Additionally, the environmental impacts of inorganic UV filters, including bioaccumulation and effects on aquatic ecosystems, warrant consideration. Advances in nanoparticle synthesis, bioactive compound integration, and environmentally friendly formulations offer pathways to enhance sunscreen efficacy and safety, providing opportunities for innovation in photoprotection.